O evolucionismo de John Rogers Commons: o processo de seleção artificial - Possamai, Adelqui Luca (2024)
The evolutionary approach outlined by John Rogers Commons diverges from the tenets of other institutionalist thinkers by emphasizing the importance of artificial selection in the context of social evolution. For Commons, the focal point of the evolutionary process lies in human will, marking a significant dissonance from the teleological perspective commonly attributed to this phenomenon. In this context, individual action is not only highlighted but also recognized as a considerable influence on the trajectory of social institutions. The primary analogy adopted by Commons is that of artificial selection, a concept originating from Darwin and employed here to delineate the distinction between mechanisms of artificial and natural selection, thereby highlighting the direct influence of human will on the evolutionary process. The core of the argument lies in the conviction that conflicts of interest are inherent in society, an inevitable consequence of material scarcity, with social institutions serving as the foundations that enable the existence of a stable social order. Within the institutional framework outlined by Commons, figures of authority emerge as holders of power and legitimacy, tasked with imposing sanctions and resolving conflicts inherent to social dynamics. In moments of conflict, the authority figure acts as an agent of selection, evaluating practices in contention in light of customs, laws, and common practices. The choice falls upon that considered as the "good practice" or the "reasonable practice," thus consolidating the influence of human will in the evolution of institutions. Under this evolutionary perspective, Commons highlights the centrality of artificial selection, where human will and the intentional resolution of conflicts of interest through institutions play fundamental roles in shaping social evolution. Equally emphasized is the non-teleological nature underlying institutional change, as the purposeful action of individuals is inherently characterized by trial and error, conferring an innovative and adaptive dynamic to the evolutionary process.